Economic growth, CO2 emissions, renewable waste and FDI relation in Pakistan: New evidences from 3SLS - Bakhsh, Khuda; Rose, Sobia; Ali, Muhammad Faisal; Ahmad, Najid; Shahbaz, Muhammad (Journal of environmental management, 2017)
First attempt has been made to find the effects of foreign direct investment on environmental pollution and economic growth, in addition to finding the determinants of foreign direct investment inflows in Pakistan using the annual data set for the period of 1980–2014. Simultaneous equation model has been used to find relation between the variables of concern. Results from technique and composition effects show that increase in economic growth leads towards more pollution emissions. Scale effect shows stock of capital and labor have positive effect on the economic growth of Pakistan while pollution has negative effect on growth. In case of capital accumulation effect, economic growth and foreign direct investment have positive and significant effect on stock of capital. Although increase in economic growth increases pollution, however, economic growth declines as pollution crosses a certain limit. Foreign direct investment is also found positively related with pollution. •Relationship between economic growth and pollution emission in Pakistan is examined.•A 3SLS model is employed.•Physical capital stock matters in economic growth.•Economic growth declines after particular level of pollution emission.